DESIGNING A MODEL FOR PHYSICAL-SPATIAL ORGANIZATION OF ECOLOGICAL ZONES WITH A GREEN SPACE CONSERVATION APPROACH (A CASE STUDY OF DISTRICT 9, ISFAHAN MUNICIPALITY) - Somayeh Hemmasian Ettefagh , Abdollah Jabalameli (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Due to the existing rules and regulations applied by different organizations and absence of optimal control by these organizations, urban ecological textures need unified ecological management that has optimal control and supervision over all these zones and make it easier for natural tourism to be in public use and earn sustainable economic and cultural income. For this reason, in this paper, a model for ecotourism management with an emphasis on urban ecological textures is provided for District 9 of Isfahan Municipality. For this reason, first, the Star method has been used as a model for interviewing experts and relevant municipal experts in Isfahan city management. The main dimensions are urban texture management, the ecological texture, ecotourism. Then, by drawing a simplified diagram of Star technique and using grounded method and combining the two approaches, a suggested model is designed according to examining the current situation, measures taken, and providing strategies in terms of urban texture management in the dimensions of ecotourism and ecological texture. Lastly, the results of ecotourism management are mentioned in all the above dimensions.